O voo do cegonho: um estudo sobre a comicidade comparativa sexual na telenovela Êta Mundo Bom! - Coelho, Thiago Henrique Fernandes (2024)
Muladeiros, tropeiros and cowboys crossed Brazil from north to south, east to west, taking cattle to trade, whether on the back of donkeys, mules or horses. This thesis also seeks to take a journey through the hills and valleys of Brazil, meeting the caipira that originated from these trips by the delegations, as well as from the settlement of the bandeirante, and the mixture with immigrants, whether European or African, and the native indigenous people of the land. Our journey has the right direction, with the destination being the comic countryman represented in the soap opera Êta Mundo Bom!, but on this path we will pass through the history of melodrama, feuilletons, radio soap operas until we reach our landing, which is the soap opera. In the same way, we will meet on this journey with the hillbillies represented in the arts throughout the 20th and 21st centuries, whether in literature, theater, cinema, comics and television. Our arrival is in the analysis of the comic scenes from the soap opera Êta Mundo Bom! based on the theories of Henri Bergson (2001) and Vladimir Propp (1992), theorists who formulated concepts to analyze comedy, how it occurs, its causes, the different types of laughter, etc. The objective of this research is to verify how the construction of the comic occurs in the soap opera chosen for the research from the country context and the play on words with the act and sexual organs, therefore, we understand it as a sexual country comedy, as the story develops on a farm in the interior of São Paulo in the 1940s, where sex generates curiosity in the young character Mafalda, and the whole family also talks about sexual practice, mainly through the metaphor of the stork, which is the name given to the male sexual organ , the female organ is called the stork's nest. The rooster's crow is always heard in certain chapters when the character Eponina and her husband Pandolfo have sexual intercourse. Therefore, we see the comic through the association with animals, a point that Vladimir Propp (1992) already points out as generating laughter. The qualitative approach to the material was based on the appreciation of the soap opera's chapters, and using as selection criteria, the scenes with the greatest comic content in relation to the country core present in the plot. The methodology used was Bardin's content analysis (2000). The way to collect the data was through the transcription of scenes from the chapters, seeking not to interfere with the way the characters speak, and subsequent analysis together with the comic theorists mentioned above.